2015
DOI: 10.1007/s00384-015-2178-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colon and rectal resections with intracorporeal anastomosis and trans-vaginal specimen extraction for colorectal cancer. A case series and systematic literature review

Abstract: Our case series, according to the results of the literature, showed that intracorporeal anastomosis associated to trans-vaginal specimen extraction is feasible and safe in selected female patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…By reducing the length of the incision, IA provides superior cosmetic results to those of EA. Attempts have also been made to combine IA with specimen extraction through a natural orifice, extracting specimens via the vagina or rectum to minimize destruction of the abdominal wall and achieve less invasiveness and better cosmetic results in a concept different from that of reduced port surgery (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…By reducing the length of the incision, IA provides superior cosmetic results to those of EA. Attempts have also been made to combine IA with specimen extraction through a natural orifice, extracting specimens via the vagina or rectum to minimize destruction of the abdominal wall and achieve less invasiveness and better cosmetic results in a concept different from that of reduced port surgery (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer is a common malignant digestive tract tumor, and usually occurs at the junction between the rectum and sigmoid colon ( 24 ). Systematic review has demonstrated that peritoneal carcinomatosis from colon cancer blocks cytoreduction and intraperitoneal chemotherapy, which requires further investigation ( 25 ).…”
Section: Discussionmentioning
confidence: 99%